Managerial Strategy in Developing Student Academic Literacy Culture Through Assistance in Writing Scientific Articles Towards Quality Scientific Publications - Afandi, Muslim; Erdayani, Rizki; Afandi, Syed Agung (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This activity aims to improve students' ability to write scientific articles, including active involvement in seminars and publication of scientific papers. The main problem behind this activity is the low understanding and contribution of students in producing quality scientific papers. This activity uses the participatory learning method. The number of participants in this activity was 30 people and came from students of the government science study program spread across the country. This community service activity was carried out online with a total of eight meetings. Based on the results of the evaluation, there was an increase in the understanding and skills of participants in writing scientific articles. However, only half of the participants were able to produce scientific articles that met the standards of accredited journals. The community service team recommends that all campuses encourage activities like this using more appropriate methods so that they have a broad impact on the participants.